Relationship of human herpes virus 6 and multiple sclerosis: A systematic review and meta‐analysis. Issue 4 (9th October 2017) - Pormohammad, Ali; Azimi, Taher; Falah, Fateme; Faghihloo, Ebrahim
Abstract : Infection with human herpes viruses has been suggested to contribute to multiple sclerosis (MS), while interaction between human herpes 6 (HHV6) and MS remain unclear yet. Here, we conducted a meta‐analysis on the relationship of HHV6 infection and MS. All related studies were collected from major databases. The analyses were performed by STATA 14 and Comprehensive Meta‐Analysis V2.0 softwares. Pooled odds ratios (ORs) and 95%CIs were calculated from the raw data of the including studies by the random effects models when I2 > 50% and fix model when I2 < 50%. Thirty nine studies were included in the meta‐analysis that 34 studies used molecular assays and 7 studies used serological assays for diagnosis of HHV6 infected cases. The relationship of HHV6 and MS was significant in healthy control group by yielding a summary OR of (2.23 [1.5–3.3], p  = 0.06). A significant HHV6 association with MS were in the studies with >6 score that used serum/blood sample with OR of (6.7 [95%CI 4.8–8.6], p  < 0.00001) and in serological studies, IgM positive titer in other neurological diseases (OND) control group was significant with OR of (8.3 [95%CI 3–24.07], p  < 0.00001). This study has been showed that there were significant relationship between MS and HHV6 infection. Abstract : Here, we conducted a meta‐analysis on the relationship of HHV6 infection and MS.This study has been showed that there were significant relationship between MS and HHV6 infection.